Analyzing the innovation ecosystem of China's major science and technology projects: From the ecological and systems science perspective - Kun Wang; Yu Feng; Siyao Liu (Project Leadership and Society)
The National Major Science and Technology Projects in China are characterized by government leadership, interdisciplinary collaboration, and international cooperation. However, challenges such as insufficient innovation capacity and inadequate commercialization of scientific achievements are becoming increasingly prominent. This paper adopts the conceptual framework of natural ecology to examine these projects. By utilizing theories and methods from ecology and systems science, we draw an analogy between the innovation ecosystem of China's national major science and technology projects and the structure of ecological systems, analyzing the interrelationships among the components of the innovation ecosystem and establishing the four-level model. The findings indicate that collaboration and policy guidance among the enterprise, research, and auxiliary innovation layers promote scientific output and innovation, while the external environmental layer provides robust support and safeguards, collectively driving the development of the innovation ecosystem. We study the operational mechanisms of the innovation ecosystem in depth, identifying mechanisms of competitive symbiosis, coordination, and sharing. These mechanisms work together throughout the project management process, offering new insights for enhancing the scientific and effective management of these projects. The national innovation ecosystem and high-quality development mutually reinforce and complement each other. As a critical pathway to high-quality development, our study provides new approaches to addressing the challenges of insufficient innovation capacity and the difficulty in translating scientific achievements into practice, contributing to the optimization of resource allocation, and the deep integration of technological innovation with economic and social development.